The Influence Of Brand Awareness, Brand Image, And Brand Trust On Brand Loyalty - Innocentius Bernarto; Margaretha Pink Berlianto; Yohana F. Cahya Palupi Meilani; Ronnie Resdianto Masman; Ian Nurpatria Suryawan (Jurnal Manajemen, 2020)
The aim of this research is to examine the positive influence of brand awareness, brand image, and brand trust on brand loyalty. The coffee shop business in big cities in Indonesia is growing rapidly. Each coffee shop strives to show its uniqueness. This competition has resulted in them competing to increase competitiveness by using logos, symbols, unique names –or what is usually called a brand to become a differentiator among the competitors. This study was done in a quantitative manner. The data was collected by using a questionnaire distributed using a survey method. Using a snowball sampling, a total of 436 samples were used and analyzed statistically using the partial least square –structural equation modeling (PLS-SEM) approach using SmartPls 3.0 program. The results show that brand awareness and brand trust had a positive effect on brand loyalty. However, the brand image did not have apositive effect on brand loyalty. This study is expected to provide input to the coffee shop management on how to increase their brand loyalty which can be done by increasing their brand awareness, brand image, and brand trust.